Spontaneous Sequestration on Oral Mucosa Associated with Removable Retainer - Azrul Hafiz Abdul Aziz; John Chong Keat Hon; Rahimah Sahudi (IIUM Press, 2024)
A 45-year-old female with Class III incisor relationship on Class I skeletal pattern came to orthodontic specialist clinic after referral from prosthodontic department. She requested to have lower dentition spaces to be closed before dental implant to be fitted. She had upper and lower dentures previously but not quite happy with the aesthetic. She is fit and healthy with diabetes mellitus type 2. Fixed appliance was done on the lower arch as the upper teeth were nicely aligned. Lower retainer was fitted after fixed appliance was removed (debonded). Several week later, she came with the complain of exposed bone on her lingual oral mucosa. The aetiology of sequestration, oral osteonecrosis and the association to diabetes mellitus is discussed in this case report.